IMPACT OF SELF ESTEEM ON TENDENCY TO FORGIVE & SPIRITUAL WELL BEING AMONG SOCIAL WORK STUDENTS IN HIGHER EDUCATION - Ranjith, G. Gayathri; V., Kalpana; A., Mathew (International Journal of Research -GRANTHAALAYAH, 2025)
Self-esteem is the confidence in one's own value, abilities, and ethics, encompassing personal beliefs. Psychologist Abraham Maslow argued that true psychological health hinges on the fundamental acceptance, love, and respect one receives from others and oneself. A healthy self-esteem enables individuals to approach life with greater confidence, kindness, and optimism, facilitating the achievement of their goals and personal growth. It is crucial for shaping emotional and psychological well-being, impacting one's ability to forgive and fostering a sense of spiritual fulfilment. In addition to their academic responsibilities, students' psychological well-being is currently a significant concern. The main focus of this research is to examine how self-esteem influences the capacity to forgive and its association with spiritual well-being, especially among social work students. This study investigates how different levels of self-esteem influence students' capacity to forgive others and sustain spiritual well-being, both of which are vital for successful practice in social work. The study employed a cross-sectional design, using Simple Random Sampling to survey a sample of 300 social work students from Anugraha Institute of Social Sciences College in Dindigul.The authors have utilized standardized questionnaires measuring self-esteem, forgiveness, and spiritual well-being using the constructed scale. The study reveals that most respondents exhibit high self-esteem (85.3%), moderate levels of forgiveness (64%), and spiritual well-being (64%), with significant correlations between forgiveness and spiritual well-being. Gender differences show females experience greater variability in spiritual well-being. Additionally, hostel residents have higher self-esteem but lower forgiveness and spiritual well-being compared to day scholars. These findings hold significant implications for educational strategies and interventions designed to enhance the psychological and spiritual well-being of social work students. By promoting a positive self-image, educational institutions can potentially enhance students' ability to forgive and improve their overall spiritual well-being, thereby equipping them with vital qualities for their future roles in social work. In the long run, this can help achieve the Sustainable Development Goals (SDGs) successfully.